First-principles Study of Vickers Hardness and Thermodynamic Properties of Ti3SnC2 Polymorphs (Journal of Scientific Research, 2015)
We have investigated Vickers hardness and the thermodynamic properties of the recently discovered nanolaminate carbide Ti3SnC2 polymorphs using the first-principles calculations. The chemical bonding shows a combination of covalent, ionic and metallic types. The strong covalent bonding is mainly responsible for high Vickers hardness of Ti3SnC2 polymorphs. Thermodynamic properties are studied using the quasi-harmonic Debye model. The variation of bulk modulus, thermal expansion coefficient, specific heats, and Debye temperature with applied pressure (P) and temperature (T) are investigated systematically within the ranges of 0 - 50 GPa and 0 - 1000 K. The calculated results have been compared with available experimental and theoretical data.